1981
DOI: 10.1161/01.str.12.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of stroke in Shibata, Japan: 1976-1978.

Abstract: SUMMARY A stroke registry was established in Shibata City, Nilgata Prefecture, Japan (population 75,000) in 1976. WHO recommendations for criteria were followed. This paper reports stroke incidence for die initial 3 years of the registry: 1976 dirough 1978. All liring padents were examined clinically by a staff physician. Only patients with a diagnosis of first stroke were included in die study. Sensitivity of the referral system was estimated at 85 + %, comparable to that in American studies.Arerage annual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
4
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 20 publications
5
58
4
1
Order By: Relevance
“…Age-specific incidence rates of first-ever stroke were also highest in Shibata, 7 closely followed by Soderhamn (1983Soderhamn ( -1984 8 and the present study. ; and Umbria, Italy, 15 were lower.…”
Section: Downloaded Fromsupporting
confidence: 70%
See 1 more Smart Citation
“…Age-specific incidence rates of first-ever stroke were also highest in Shibata, 7 closely followed by Soderhamn (1983Soderhamn ( -1984 8 and the present study. ; and Umbria, Italy, 15 were lower.…”
Section: Downloaded Fromsupporting
confidence: 70%
“…The incidence rates of first stroke in our study, age and sex adjusted to the Danish population in 1982, are relatively high. Rates from Shibata, Japan, 7 Soderhamn, Sweden, 8 were higher, whereas rates were lower in the other "ideal" studies. 8 - 13 The high rates in our study can be explained only partially by the high proportion of older people in the Danish population.…”
Section: Downloaded Frommentioning
confidence: 74%
“…[7][8][9][10][11][12][13][14][15][16] Previous studies in China, Hong Kong, Taiwan, and Japan generally found that 23% to 52.2% of strokes were hemorrhagic, [3][4][5][6][21][22][23][24][25] in contrast to only 9% to 18% in whites. [7][8][9][10][11][12][13][14][15][16] In the present study, 29.6% of stroke cases overall in 2000 were hemorrhagic in Chinese populations, which supported the above idea that an ethnic difference existed between Eastern and Western populations.…”
Section: Stroke Subtypes In Chinese Populations Compared With Westernmentioning
confidence: 99%
“…2,3 The natural history and pathogenesis of perihematomal edema in human spontaneous intracerebral hemorrhage (SICH) are just beginning to be understood, particularly in the hyperacute setting. Carefully documenting the genesis and evolution of edema is a necessary first step in understanding the pathogenesis of edema and whether it might be altered by treatment strategies aimed at reducing edema-related morbidity and mortality.…”
mentioning
confidence: 99%
“…This study is a secondary analysis of data prospectively collected during a population-based study of hematoma growth after hyperacute SICH, whose original results have been previously reported. 4 Patients in this study systematically underwent baseline CT scanning within 3 hours of clinical ICH onset, with repeated studies at 1 and 20 hours after baseline CT. We sought (1) to summarize edema volumes in both absolute and relative terms (see below) and (2) to explore the presence of associations between edema volume and relevant clinical and radiological variables.…”
mentioning
confidence: 99%